The girl with more than one heart - Geringer, Laura, 1948- (Amulet Books, 2018)
Briana, devastated by the sudden death of her dad, imagines she has a new heart growing deep inside her belly that gives advice in her father's voice, providing her with the support she needs to navigate through her grief.